TINJAUAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEKERJAAN PROYEK PEMBANGUNAN JALAN TRANS SERAM BAGIAN BARAT (STA 0+000-9+300) - Semuel Uneputty; Glen Boyke Rehatta (Journal Agregate, 2022)
West Seram Regency is one of the regencies in Maluku province, Indonesia. This district has a population of 212,393 in 2020 and its people are of very diverse backgrounds, both ethnic and religious. Meanwhile, the government center is in Piru, part of West Seram District, which has a population of 16,628 people. Huamual Rear District, which is the location of the Trans Seram road construction project, is a sub-district in West Seram Regency, Maluku, Indonesia. The Trans Seram road construction project, which is located from Limboro Hamlet - Ulatu Hamlet, Huamual Rear District, includes 5 hamlets including Limboro Hamlet, Temi Hamlet, Erang Hamlet, Tapinalu Hamlet, and Ulatu Hamlet. with a project length of up to 9.3 KM. The data analysis technique uses the descriptive method with the help of the SPSS program. Descriptive method is to provide an overview of research subjects based on variable data from the group of subjects studied.The results of this study can be concluded that in general the implementation of occupational safety and health in the Western Part of the Trans Seram Road Development Project is not good. Then the application of K3 in the drainage work was not good, the 2nd layer spreading and compaction work was not good, the paving work was not good, and the material transport work was not good. This was evidenced by the results of the descriptive statistical test (t-test) which rejected the initial hypothesis (H0). Occupational Safety and Health (K3) on the Western Part of the Trans Seram Road Construction Project Seen from the Attitude of Workers. From the descriptive analysis it can be concluded that the workers in the Western Part of the Trans Seram Road Construction Project have a positive attitude towards the Application of K3 in the Western Trans Seram Road Construction Project, positive attitudes are also triggered because the workers have good knowledge so that automatically their attitude also Good.